Phenomenology study: sexual behavior of teenager with intellectual disability in Bantul, Yogyakarta - Rahmah Widyaningrum (STIKep PPNI Jawa Barat, 2021)
Aims: to characterize sexual behavior of teenagers with intellectual disability in Bantul, Yogyakarta. Design: Cross sectional study with qualitative approach using phenomenology. Methods: Data were collected using in-depth interview according to structured interview guidelines and observation sheet. Subjects were 2 teachers and 5 students in SLB Negeri 1 Bantul that were selected using purposive sampling method. Data were analyzed using inductive method and Colaizzi’s synthesis method. All analyses were performed in Open Code version 3.6.2.0. Results: Teenagers with intellectual disability comprehend sexuality as touching prohibition between men and women. Adultery indicator was assessed by the presence of nocturnal emission in men or menstruation in women. Some sexual behavior that was shown by teenagers with intellectual disability are holding hands, hugging, masturbation in men and sexual intercourse. Degree of sexual behavior was depended on disability severity. Conclusions: Sexual behavior was rise due to desire in teenager with intellectual disability. Pornographic video, accessed from cell phone, was strong stimulus that impact sexual behavior. Controlling negative sexual behavior through religion and norm, music and outdoor activity were used by teacher.